Taking stock: A multistakeholder perspective on improving the delivery of care and the development of treatments for Alzheimer's disease. Issue 4 (21st April 2014) - Bradley, Patrick; Akehurst, Ron; Ballard, Clive; Banerjee, Sube; Blennow, Kaj; Bremner, Jennifer; Broich, Karl; Cummings, Jeffrey; Dening, Karen; Dubois, Bruno; Klipper, Wiebke; Leibman, Chris; et al.
Abstract: Health‐care stakeholders increasingly recognize that the scientific and economic challenges associated with Alzheimer's disease (AD) are simply too great for individual stakeholder groups to address solely from within their own silos. In the necessary spirit of collaboration, we present in this perspective a set of multicountry multistakeholder recommendations to improve the organization of existing AD and dementia care and the development of new treatments. In brief, the five recommendations are (1) health‐care systems must make choices regarding the patient populations to be diagnosed and treated, (2) health‐care systems should use an evidence‐based standard of care, (3) increased collaboration between public and private institutions is needed to enhance research, (4) reimbursement end points need to be agreed on and validated, and (5) innovative business models should be used to spur the introduction of new medicines.